Effect of N, P and K on yield of wheat under well irrigation in undifferentiated alluviums of Rajasthan - Jaisinghani, C J; Mehta, K. M. (Journal of Soil and Water Conservation, 2022)
In Rajasthan, wheat is the most important rabi crop growing under a variety of soils, out of which undifferentiated alluviums represents important soil group. The crop is mostly taken under irrigated con- ditions of which wells are the main sources and the yields are low. Thus any improvement brought about in the yield under well irri- gation, would mean a substantial increase in total production under this crop. Since very little informa- tion was available with regard to response of different fertilizers under the above soils under well irrigation, an experiment was conducted with various fertilisers applied at different levels at Government Agricultural Farm, Tabiji to find out the optimum dose for maximum and economical production.